Navigating the Boundaries of Understanding: Methodological Reflections on Cross-Cultural Challenges in Reconstructive Social Research - Ana Mijić (International Journal of Qualitative Methods)
Qualitative researchers often face ethical and practical challenges when engaging participants across linguistic and cultural boundaries. These challenges arise at various stages of the research process, from obtaining genuine informed consent and selecting appropriate interview languages to determining whether data should be analyzed in its original language or translated. However, interpretive and reconstructive approaches—aimed at analyzing the subjective, social, or latent meanings embedded in participants’ expressions—encounter the additional difficulty of deriving valid insights when interviewees and interpreters come from different experiential backgrounds or when data is collected in a language unfamiliar to the researcher. Drawing on the contradictory theoretical considerations of Alfred Schütz and Ulrich Oevermann regarding the understanding of the other and integrating these perspectives, this paper advocates for ongoing dialogue between external outsider viewpoints and the insider perspectives of culturally familiar co-interpreters, who can serve as reconstructive translators in the analysis. This paper draws on three case studies to illustrate how we addressed cross-cultural and cross-linguistic challenges in specific research settings. It concludes that while universal solutions are elusive, it is crucial to understand that, given the growing diversity of societies, cross-cultural challenges can arise even in research contexts not explicitly defined as cross-cultural. Therefore, it is essential that all research projects engage in a thorough reflection on positionality and the analytical standpoint. Based on this reflection and the insights that arise, researchers should formulate customized strategies to effectively navigate cross-cultural and cross-linguistic challenges in every reconstructive social research project.